Towards a gender-sensitive model for distance education planning - Koyali Burman (Adult Education Research Conference, 2006)
Development projects are vehicles for generating change. Since last century, the world has experienced unprecedented economic expansion and more interest in the development with emphasis on the capacity-building and sustainability of projects. As a result there is a considerable increase of technological progress and more intense international competition. A common refrain in many circles is that gender principles are often discussed, but seldom applied.